Using Big Data to Expand Financial Services : Benefits and Risks - Abraham, Facundo (World Bank, Washington, DC, 2019)
Big data is transforming financial services around the world. Advances in data analytics and computational power are allowing firms to exploit data in an easier, faster, and more reliable manner, and at a larger scale. By using big data, financial firms and new entrants from other sectors are able to provide more and better financial services. Governments are also exploring ways to use big data collected by the financial sector more systematically to get a better picture of the financial system as a whole and the overall economy. Despite its benefits, the wider use of big data has raised concerns related to consumer privacy, data security, discrimination, data accuracy, and competition. Hence, policy makers have started to regulate and monitor the use of big data by financial institutions and to think about how to use big data for the benefit of all.